Development of a methodological approach to the research of special purpose communication systems - Semenenko, Inha; Artabaiev, Yurii; Degtyareva, Larisa; Vakulenko, Yuliia; Odarushchenko, Elena; Nalapko, Oleksii; Zarubenko, Artur; Pavliuk, Dmytro; Demianenko, Hanna; Kovalchuk, Bohdan (Technology audit and production reserves, 2022)
Hierarchical construction of special purpose systems, a large number of different types of communication devices that are the part of them necessitates the need to justify the order of research of special communication systems. Existing approaches to conduct research on special purpose communication systems are narrowly focused and aimed at researching certain types of communication. A large number of destabilizing factors affecting the functioning of special purpose communication systems and a priori uncertainty about the conditions of its application only complicate the mentioned issue. Also, the experience of the full-scale armed aggression of the armed forces of the Russian Federation on the territory of Ukraine showed the need to change approaches to the research of special purpose communication systems. That is why the issue of improving the effectiveness of the management of forces and devices of communication of groups of troops (forces) during operations is an important and urgent issue. The object of the research is the communication system of the group of troops (forces). The subject of the research is the effectiveness of the communication system of the group of troops (forces) in accordance with the purpose of the operation. The research developed a methodical approach to the research of special purpose communication systems. The novelty of the proposed methodical approach consists in taking into account the efficiency while choosing this or that method while investigating the state of a special-purpose communication system and the ability to calculate the reliability while choosing this or that method while investigating the state of a special-purpose communication system. Also, the element of novelty of this methodical approach is taking into account the efficiency of the decisions made regarding the assessment of the state of the special purpose communication system while choosing one or another research method. It is advisable to implement the mentioned approach in algorithmic and program software while studying the state of the special purpose communication system.